An SEM flashover: technique to characterize wide band gap insulators - Sutjipto, Agus Geter Edy; Muhida, Riza; Takata, Masasuke (2006)
This paper introduces the use of a scanning electron microscope (SEM) to evaluate the insulation property of wide band gap insulators. An SEM may be used not only to observe a surface image but also to provide a fine electron beam for charging an uncoated insulator surface at once. The charging can create an electric field distribution in the surface. The increase of electric field at the surface may exceed a critical value when a surface breakdown/flashover occurs. An insulation property can be evaluated by varying the duration of charging/electron bombardment which is needed to initiate an optically-visible flashover treeing formation (hereinafter time to flashover treeing/TTF). In this paper, high purity MgO as a wide band gap insulator material was used as a main investigated sample. Varying addition of high purity SiO2 was used to change insulator property of the MgO. Under a certain SEM's energy and magnification, SiO2 addition has change the duration of charging up to surface breakdown. Therefore, this technique may be useful for investigating an insulation property of materials under electron bombardment such as MgO in a plasma display panel, high voltage insulator, and other insulator materials for space technology.